Perancangan Sistem Otomatis Update Pada Aplikasi Desktop Abios - Iskandar, Karto (Bina Nusantara University, 2010)
Unlike web applications easier to update the latest version, desktop applications more difficult and must involve the user in doing so. It is caused by a desktop application is an application that is installed in the computer user. The purpose of this research is to design an automatic system updates on a desktop application, an example case: Application Binus International Operational Support (ABIOS). This research used literature study and system design. In desktop applications, often there is update the latest applications that are not known to the user who sometimes fatal and disrupt business operations. Generally, developer will inform the changes version to user that they can update the application. In an update of applications, should be done by the system automatically, not manually by users. Once in a while, the user background is not from computer base. After doing the research, it can be concluded that the system automatically updates the application has benefits to users in obtaining information regarding the latest version, and can assist in automatically update the latest application is based on computerization. For further development of this system is expected to operate on multi platforms and or mobile applications.